2020
DOI: 10.1016/j.cell.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Dual Functions of a Rubisco Activase in Metabolic Repair and Recruitment to Carboxysomes

Abstract: Rubisco, the key enzyme of CO 2 fixation in photosynthesis, is prone to inactivation by inhibitory sugar phosphates. Inhibited Rubisco undergoes conformational repair by the hexameric AAA+ chaperone Rubisco activase (Rca) in a process that is not well understood. Here, we performed a structural and mechanistic analysis of cyanobacterial Rca, a close homolog of plant Rca. In the Rca:Rubisco complex, Rca is positioned over the Rubisco catalytic site under repair and pulls the N-terminal tail of the large Rubisco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 110 publications
1
21
0
Order By: Relevance
“…All relevant biochemical experiments were replicated two or three times. No statistical methods were used to predetermine sample size, but our sample sizes are similar to those reported in previous publications 16 , 19 . For cryo-EM, data were screened on eight independently prepared samples.…”
Section: Methodsmentioning
confidence: 64%
See 2 more Smart Citations
“…All relevant biochemical experiments were replicated two or three times. No statistical methods were used to predetermine sample size, but our sample sizes are similar to those reported in previous publications 16 , 19 . For cryo-EM, data were screened on eight independently prepared samples.…”
Section: Methodsmentioning
confidence: 64%
“…The restructuring of the pre-carboxysome condensate following oxidation may promote the formation of channels around the Rubisco lattice that can be navigated by other carboxysomal proteins and metabolites. This would also facilitate the metabolic repair of Rubisco by Rubisco activase, which possesses SSUL modules for recruitment into the pre-carboxysome matrix 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bacterial carboxysomal α-system, we have demonstrated that Rubisco binds the intrinsically disordered proteins CsoS2 (26) and CsoSCA. Additionally, it also binds the Rubisco activase CbbQO, likely via CbbO's von Willebrand factor A domain (36,37) The β-carboxysomal Rubisco binds its interaction partners, the scaffolding protein CcmM (38) (39), and the Rubisco activase Rca (40,41), via a folded domain resembling the small subunit of Rubisco. Despite convergent evolution, a notable similarity between both carboxysome systems is the binding site on Rubisco.…”
Section: Rubisco As An Interaction Hub In Biophysical Ccm'smentioning
confidence: 99%
“…With regards to Form IB Rubisco, it has very recently been shown that the Rca-like protein found in some cyanobacterial clades (38,39) is a functional Rubisco activase in Nostoc sp. PCC7120 (40).…”
Section: Introductionmentioning
confidence: 99%